Silibinin upregulates E-cadherin expression in MKN-45 human gastric cancer cells - Ebrahim Faghihloo*; Habibollah Mirzaei; Abolfazl Akbari; Hossein Goudarzi (Iranian Society of Pharmacognosy, 2018)
Background and objectives:  Gastric cancer is currently known as one of the most important causes of cancer-driven death all over the world. In patients with gastric cancer, a significant proportion of death occurs due to metastasis. On the other hand, down modulated E-cadherin level has been reported as an important contributor to tumor cell invasion and metastasis. In this regard, the present work was aimed to evaluate the impact of silibinin, a flavonolignan with established anti-tumor efficacy, on cell viability and E-cadherin expression in the gastric cancer cell line MKN-45. Methods: To determine cell viability, MTT assay was performed 48 h after silibinin treatment (at concentrations of 100, 200 and 400 μM). In addition, quantitative real-time PCR was done following total RNA extraction and cDNA synthesis, to assess E-cadherin level in cells treated with silibinin. Results: The MTT results showed concentration-dependent reducing effect of silibinin on viability of MKN-45 cells. The findings of quantitative real-time PCR analysis demonstrated upregulated E-cadherin expression in cells treated with silibinin (significantly (p≤ 0.05) at concentration of 200 μM) compared to the control cells. Conclusions: The current study suggested that silibinin may exert anti-migratory/invasive effects on gastric cancer cells by enhancing E-cadherin expression, which needs to be further investigated.